A. To add 3.2 x 10^4 and 1.95 x 10^6, we first need to make sure that the exponents are the same. We can do this by converting 3.2 x 10^4 to scientific notation with the exponent of 6:
3.2 x 10^4 = 3.2 x 10^(4+2) = 3.2 x 10^6
Now, we can add the numbers:
3.2 x 10^6 + 1.95 x 10^6 = (3.2 + 1.95) x 10^6 = 5.15 x 10^6
Therefore, the result is 5.15 x 10^6.
B. To subtract 1.95 x 10^6 and 3.2 x 10^4, we again need to make sure the exponents are the same. We can convert 3.2 x 10^4 to scientific notation with the exponent of 6:
3.2 x 10^4 = 3.2 x 10^(4+2) = 3.2 x 10^6
Now we can subtract the numbers:
1.95 x 10^6 - 3.2 x 10^6 = (1.95 - 3.2) x 10^6 = -1.25 x 10^6
Therefore, the result is -1.25 x 10^6.
C. To multiply 3.2 x 10^4 and 1.95 x 10^6, we need to multiply the numbers and add the exponents:
3.2 x 10^4 * 1.95 x 10^6 = (3.2 * 1.95) x 10^(4+6) = 6.24 x 10^10
Therefore, the result is 6.24 x 10^10.
D. To divide 1.95 x 10^6 by 3.2 x 10^4, we need to divide the numbers and subtract the exponents:
1.95 x 10^6 / 3.2 x 10^4 = (1.95 / 3.2) x 10^(6-4) = 0.609375 x 10^2
Since 0.609375 is already in decimal form, we can rewrite it as 6.09375 x 10^(-2+2) = 6.09375 x 10^0 = 6.09375
Therefore, the result is 6.09375 x 10^0.
use 3.2x10^4 and 1.95 x 10^6 for steps a,b,c,d. Answers MUST be in correct scientific notation. show work
A. Add 3.2 x 10^4 and 1.95 x 10^6
B. Subtract 1.95 x 10^6 and 3.2 x 10^4
C. Multiply 3.2 x 10^4 and 1.95 x 10^6
D. Divide 1.95 x 10^6 and 3.2 x 10^4
1 answer